A hedonic analysis of the value of rail transport in the greater Dublin area - Karen Mayor; Seán Lyons; David Duffy; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2008)
We use a hedonic house price model to estimate the value of transport networks to homeowners in the Dublin area. Using a dataset of house sales between 2001 and 2006 and combining it with available geographical information system data on the train and tram lines in Dublin, it is possible to assess the values assigned to different transport links by homeowners. We find that the value of transport depends on how far from the property it is located and is also affected by the availability of alternative transport options in the area. There are differences in the values assigned to recently constructed tramlines compared to the traditional rapid transit train stations. The study also takes into account house characteristics and other environmental amenities.
Keywords: 330; hedonic regression; train; tram; transport network; Ireland; geographical information system; Öffentlicher Personennahverkehr; Bewertung; Grundbesitz; Städtischer Immobilienmarkt; Immobilienpreis; Dublin